"Galanteo de mozo e moza", an 18th Galician Romance: Edition and Study - Álvarez, Rosario (Madrygal. Revista de Estudios Gallegos, 2018)
The aim of this contribution is to bring to light a poetic composition (romance) written in the Galician language in the 18th century. At the beginning of the 20th century, the text was reported, but not published, and had been missing until recently. It is part of the manuscript volume Ocios poéticos..., a compilation of Father Feijoo’s literary papers, mostly poetic compositions of the Benedictine sage, gathered after his death. Among the objectives, it is also to discuss the arguments as regards the possible authorship and dating of the text, which comes to increase the diminished tradition of writing in Galician during the “séculos escuros” (the “dark centuries”: 16th -18th centuries). The paper presents an editing of the text and studies its language, both intrinsically and by comparison with that of the other authors of the period called Middle Galician, taking as basis the Gondomar corpus, recently opened to public consultation. We place it in the context of continuity between medieval tradition and modern results, in a perspective of variation that always combines the diachronic with the diatopic vision. The analysis of the lexicon has also allowed us to highlight on some aspects which may be interesting for the history of Galician culture. The conclusion of the current study is that the text does not belong to Father Feijoo, who should have only intervened only in the final linguistic note and, perhaps, in the marginal glosses. As regards the dating, we have placed it provisionally in the middle of the 18th century.